Response to Levetiracetam Treatment and Long-Term Follow-Up in Dogs With Reactive Seizures Due to Probable Exogenous Toxicity - Fabio Stabile (Frontiers Media S.A., 2021)
Limited information is available on the long-term follow-up and seizure recurrence in dogs with reactive seizures due to suspected exogenous toxicity. The purpose of this study was to report the long-term follow-up of 13 dogs referred to a single referral hospital, diagnosed with reactive seizures and treated with a standardized levetiracetam protocol. All dogs received a loading levetiracetam dose of 60 mg/kg/IV once, followed by a maintenance dose of 20 mg/kg every 8 h as part of an open-label clinical study. Levetiracetam was withdrawn after a 6-months seizure-free period by reducing levetiracetam to 20 mg/kg every 12 h for a 4-week seizure-free period, followed by levetiracetam 20 mg/kg every 24 h for a 4-week seizure-free period, before levetiracetam treatment was stopped. No adverse effects of the treatment were reported. No dogs experienced any seizures after discharge or after levetiracetam withdrawal. Median follow-up time from time of discharge was of 78 months (=6 years 6 months). The result of this study supports the use of levetiracetam for treatment of reactive seizures due to exogenous substance intoxication. Moreover, our results do not support the need for long-term antiepileptic treatment in cases of reactive seizures due to exogenous intoxication.